Institutional context of specialist counseling – discussion of research; circumstances for change - Zaborowska, Agnieszka (Research Papers of Wrocław University of Economics, 2018)
The aim of the article is to indicate the reasons for institutional changes in the provision of specialist counseling services in Poland. The author poses a thesis that specialist counseling is too closely associated with the social assistance system and becomes synonymous with social counseling. This results in lack of universality of the service which is directed almost exclusively to beneficiaries of social security. In the meantime, specialist counseling should “overtake” the social security system and act immediately after the problem has been identified, in the early stages of a difficult situation. The article is of analyticalempirical nature. The presented position results from the quantitative and qualitative analysis of research carried out among representatives of social services, specialists, local authorities, representatives of the III sector, people managing social security systems and local communities
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2018, Nr 510, s. 193-206
Keywords: specialist counseling; social counseling; social security; poradnictwo specjalistyczne; poradnictwo socjalne; pomoc społeczna